Kaatsu training to enhance physical function of older adults with knee osteoarthritis: Design of a randomized controlled trial - Buford, Thomas W. (Contemp Clin Trials, 2015)
As the U.S. population ages, efficacious interventions are needed to manage pain and maintain physical function among older adults with osteoarthritis (OA). Skeletal muscle weakness is a primary contributory factor to pain and functional decline among persons with OA, thus interventions are needed that improve muscle strength. High-load resistance exercise is the best-known method of improving muscle strength; however high-compressive loads commonly induce significant joint pain among persons with OA. Thus interventions with low-compressive loads are needed which improve muscle strength while limiting joint stress. This study is investigating the potential of an innovative training paradigm, known as Kaatsu, for this purpose. Kaatsu involves performing low-load exercise while externally-applied compression partially restricts blood flow to the active skeletal muscle. The objective of this randomized, single-masked pilot trial is to evaluate the efficacy and feasibility of chronic Kaatsu training for improving skeletal muscle strength and physical function among older adults. Participants aged ≥ 60 years with physical limitations and symptomatic knee OA will be randomly assigned to engage in a 3-month intervention of either (1) center-based, moderate-load resistance training, or (2) Kaatsu training matched for overall workload. Study dependent outcomes include the change in 1) knee extensor strength, 2) objective measures of physical function, and 3) subjective measures of physical function and pain. This study will provide novel information regarding the therapeutic potential of Kaatsu training while also informing about the long-term clinical viability of the paradigm by evaluating participant safety, discomfort, and willingness to continually engage in the intervention.